Antitumor effects of histone deacetylase inhibitor suberoylanilide hydroxamic acid in epidermal growth factor receptor-mutant non-small-cell lung cancer lines in vitro and in vivo. Issue 3 (March 2018) - Wei, Ye; Zhou, Fangzheng; Lin, Zhenyu; Shi, Liangliang; Huang, Ai; Liu, Tao; Yu, Dandan; Wu, Gang
Abstract : Histone acetylation is one of the most abundant post-translational modifications in eukaryotic cells; aberrant histone acetylation is related to a range of cancer types because of the dysregulation of histone deacetylases (HDACs). Inhibition of HDACs leads to suppression of tumor growth in multiple cancers, whereas the inhibitory effects of HDAC inhibitors remain incompletely understood in epidermal growth factor receptor (EGFR)-mutant lung cancers. In this study, the antitumor effects of HDACs inhibitor suberoylanilide hydroxamic acid (SAHA, vorinostat) were examined in EGFR-mutant lung cancer cell lines. The results of the present work showed that SAHA markedly inhibited cell viability and proliferation, induced cell apoptosis by arresting the cell cycle in the G2 /M phase, and significantly reduced tumor growth in a xenograft model. Further study confirmed that the suppression function of SAHA might be mediated by regulating the ERK-dependent and/or the AKT-dependent pathway; meanwhile, angiogenesis abrogation induced by SAHA exerted effects on tumor regression in vivo . Taken together, our results identify the antitumor effects of HDACs inhibitor SAHA as an alternative therapeutic application for the epigenetic treatment of EGFR-mutant non-small-cell lung cancer.